PGM Protocol-pragmatic general multicast its application in file transfer service - Marrone, Luis Armando; Abeledo, María Claudia (2007)
The aim of this article is to explain new projects ta- king place about secure file transfer techniques by multicast. In this matter we will analyze Pragmatic General Multicast as a way to obtain better results in terms of transfer rate and a development in the way of using net resources. To conclude, there will be a com- parison among the results of this specific file transfer and the FTP over TCP conventional technology.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Electronics, Robotics and Automotive Mechanics Conference. CERMA 2007 (2007, Sep. 25-28 : Morelos, México), IEEE, 2007. pp. 15-20.
Keywords: TCP/IP